52 Access to non-standard treatments: Insights from a UK-wide review of adult brain tumour services (2024-2026) - Joanne Lewis; Andrew Wright; Eloise Lines; Camille Goetz; Nicky Huskens (Neuro-Oncology, 2026)
Abstract Introduction Patients with high grade primary brain tumours often face poor outcomes and limited treatment options. Access to non-standard treatments - interventions not routinely available or funded for this patient group - may offer opportunities to improve survival and quality of life. Access routes include individual funding requests (IFRs), clinical trials, and early/managed access programmes. We aimed to examine variation in access to non-standard treatments across UK adult brain tumour services. Method Data were collected from 24 NHS neuro-oncology centres (covering >90% of the UK population) through the Tessa Jowell Centre of Excellence programme (2024–2026). Quantitative data were analysed descriptively, and qualitative findings were analysed thematically. Results Only 45% centres (11/24) reported a successful IFR (or equivalent) in the past year. Reported barriers included low success rates (12/24, 50%), time burden (8/24, 33%), and treatment delays (4/24, 17%). Many centres reported using alternative routes: early access schemes (9/24), clinical trials (6/24), managed access programmes (4/24), and hospital funding (3/24). Centres in the devolved nations reported fewer barriers overall and submitted significantly more successful requests than English centres. Centres reported offering 21 non-standard treatments, most commonly ONC201 (8/24), dabrafenib/trametinib (7/24), bevacizumab (6/24), and vorasidenib (5/24). Treatments centres wanted to, but were not able to, provide included bevacizumab (11/24), dabrafenib/trametinib (9/24), vorasidenib (7/24), and Tumour Treating Fields (6/24). Conclusions Centres reported substantial variation in the routes used to access non-standard treatments. Varying IFR success rates and reliance on alternative local schemes may contribute to inequitable access. Further work by the Tessa Jowell Brain Cancer Mission and its partners, such as an upcoming position statement on access to bevacizumab to treat radionecrosis, will focus on reducing this variation and standardising access.